Community assistance in the establishment of an educational tour of Kampung Sutera - Mas'ud, M. Imron; Zahro, Mir’atuz; Setiawan, Bayu; Putri, Widya Lestari; Kurniasari, Nurul Sandra; Fauzi, Achmad; Risma, Nafiatul; Nafisah, Jauharotun (Universitas Muhammadiyah Magelang, 2021)
The existence of educational tourism is increasingly needed by the community. In addition to the limited number, educational tourism also has a strategic role such as being able to help increase the income of the surrounding community. This community service aims to empower the community through assistance in establishing an educational tour of Kampung Sutera in Sentul Village, Purwodadi District, Pasuruan Regency. This service method was carried out through FGDs, surveys, interviews, mapping, and training. This service activity gets community support, so that Kampung Sutera can be realized and will have a positive impact on the community's economy. In addition, the existence of Kampung Sutera is also supported by the existence of a website as a promotional medium.